CERTAIN FEATURES OF ELECTRICAL SUPPLY OF ELECTROCHEMICAL PROTECTION DEVICES OF HIGH PRESSURE OIL AND GAS PIPES - Rakhmatov Davron; Rakhmanov Ikhtiyor; Bobomurodova Mekhriniso (International Journal of Innovations in Engineering Research and Technology, 2021)
The article provides information on the process of corrosion of high-pressure oil and gas pipelines, methods of combating it and devices for the implementation of the process.